Reactive oxygen: A novel antimicrobial mechanism for targeting biofilm-associated infection. (March 2017) - Dryden, Matthew S.; Cooke, Jonathan; Salib, Rami J.; Holding, Rebecca E.; Biggs, Timothy; Salamat, Ali A.; Allan, Raymond N.; Newby, Rachel S.; Halstead, Fenella; Oppenheim, Beryl; Hall, Thomas; Cox, Sophie C.; et al.
Highlights: Reactive oxygen species (ROS) delivered by engineered honey or gel. Novel antimicrobial with activity against all bacteria as well as antifungal and antiviral activity. Topical treatment with antibiofilm activity. Therapeutic implications for wound healing and possibly mucosal infection in respiratory and urinary tract. Topical and local applications but could be applied to internal mucosal structures. Abstract: Reactive oxygen species (ROS) is a novel therapeutic strategy for topical or local application to wounds, mucosa or internal structures where there may be heavy bacterial bioburden with biofilm and chronic inflammation. Bacterial biofilms are a significant problem in clinical settings owing to their increased tolerance towards conventionally prescribed antibiotics and their propensity for selection of further antibacterial resistance. There is therefore a pressing need for the development of alternative therapeutic strategies that can improve antibiotic efficacy towards biofilms. ROS has been successful in treating chronic wounds and in clearing multidrug-resistant organisms, including methicillin-resistant Staphylococcus aureus (MRSA), and carbapenemase-producing isolates from wounds and vascular line sites. There is significant antifungal activity of ROS against planktonic and biofilm forms. Nebulised ROS has been evaluated in limited subjects to assess reductions in bioburden in chronically colonised respiratory tracts. The antibiofilm activity of ROS could have great implications for the treatment of a variety of persistent respiratory conditions. Use of ROS on internal prosthetic devices shows promise. A variety of novel delivery mechanisms are being developed to apply ROS activity to different anatomical sites.